2009
DOI: 10.1128/mcb.00199-09
|View full text |Cite
|
Sign up to set email alerts
|

Cdo Binds Abl To Promote p38α/β Mitogen-Activated Protein Kinase Activity and Myogenic Differentiation

Abstract: The p38 mitogen-activated protein kinase (MAPK) pathway is required for differentiation of skeletal myoblasts, but how the pathway is activated during this process is not well understood. One mechanism involves the cell surface receptor Cdo (also known as Cdon), which binds to Bnip-2 and JLP, scaffold proteins for Cdc42 and p38, respectively; formation of these complexes results in Bnip-2/Cdc42-dependent activation of p38. It has been reported that the tyrosine kinase Abl promotes myogenic differentiation in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
71
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(77 citation statements)
references
References 54 publications
5
71
1
Order By: Relevance
“…Even though extracellular activation of PI3K/Akt by receptor tyrosine kinases (such as the IGF-IR) is well established, the stimuli that activate p38 MAPK have been more elusive. The importance of cell-cell contact in the activation of p38 has recently been identified (18,19). We have further demonstrated that cross communication between PI3K/Akt and p38 MAPK is necessary for efficient myoblast differentiation (11), thus integrating extracellular signals.…”
mentioning
confidence: 54%
“…Even though extracellular activation of PI3K/Akt by receptor tyrosine kinases (such as the IGF-IR) is well established, the stimuli that activate p38 MAPK have been more elusive. The importance of cell-cell contact in the activation of p38 has recently been identified (18,19). We have further demonstrated that cross communication between PI3K/Akt and p38 MAPK is necessary for efficient myoblast differentiation (11), thus integrating extracellular signals.…”
mentioning
confidence: 54%
“…6K). In our recent report (43), the non-receptor tyrosine kinase Abl interacts with the cytoplasmic region of Cdo and JLP and cooperates with JLP and Cdo to activate p38MAPK and promote myoblast differentiation. It is possible that Abl may be responsible for activating ASK1 and TAK1 to initiate the downstream signaling pathway.…”
Section: Discussionmentioning
confidence: 88%
“…It is possible that Abl may be responsible for activating ASK1 and TAK1 to initiate the downstream signaling pathway. However Abl may not act solely as a kinase in this context, as a kinasedeficient mutant form of Abl retains partial activity in stimulating p38MAPK activity (43). Based on these data, we propose that N-cadherin-mediated cell contact may induce a complex formation of Cdo with JLP, ASK1/TAK1, and p38MAPK, thereby enhancing the activation of p38MAPK.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Myoblast C2C12 cells, embryonic fibroblast 10T1/2 cells and embryonic kidney 293T cells were cultured as described previously [14, 15]. To induce differentiation of C2C12 myoblasts, cells at near confluence were switched from DMEM containing 15% FBS (fetal bovine serum; growth medium, GM) to DMEM containing 2% HS (horse serum; differentiation medium, DM) and myotube formation was observed normally at approximately 2–3 days of differentiation.…”
Section: Methodsmentioning
confidence: 99%